The theory of compulsion (Ijbar) in marriage under Islamic law:iIncorporation of the Hanafis view on compulsory consent in marriage under the Islamic family law (Federal Territories) Act 1984 - Mohd, Azizah; A. Kadir, Nadhilah (2019)
Under Islamic law, a wali mujbir has an authority to contract the marriage of his virgin daughter even though she does not agree with the marriage. The authority is known as wilayat al-ijbar and quite often described as marriage by compulsion. This paper seeks to examine the theory and concept of compulsion in marriage or ijbar under Islamic law. Discussion will include analysis on views of classical and contemporary Muslim scholars on the issue.. The paper will also investigate the practice and views of the Muslim communities in Malaysia nowadays as regards to marriage by compulsion based on the theory of ijbar. Examination will extend to the provisions of Islamic Family law (Federal Territories) Act 1984 on compulsory consent of a woman in her marriage that follows the view of the Hanafis. The research will adopt a qualitative research where most of the materials will be based in the library. Finally, the research will provide suggestion for improvement of the application of Islamic law in Malaysia especially on incorporation of the views of sunni school other than Shafi’is, where relevant and necessary.